The quantitative assessment of water erosion in the southeast of Central Rif – Morocco - Senhaji, Mohamed; Abahrour, Mohamed; Hmamouchi, Mostafa; Abahrour, Younes (Arab Journal for Sciences and Research Publishing, 2024)
Water erosion is considered one of the most significant environmental hazards threatening the stability of natural environments worldwide, especially in arid and semi-arid areas such as the Rif Mountains in Morocco. In these regions, substantial amounts of soil, particularly fine particles, are eroded, leading to a decline in soil fertility in agricultural areas and subsequently reducing their productivity. Addressing this phenomenon requires the adoption of various methods and approaches, including the quantitative assessment of water erosion based on the Universal Soil Loss Equation (RUSLE). This equation works to mitigate sheet erosion by examining the natural and human factors responsible for the dynamics of water erosion. It aims to determine the quantity of lost soil based on different factors, utilizing geographic information systems and remote sensing techniques. The rate of soil loss in the Oued Broun watershed is recorded at 29.4 tons per hectare per year, with variations from one area to another within the watershed due to differences in the factors responsible for soil loss in the region. The aim of this study is to classify the watershed based on the degrees of soil degradation risk, providing assistance to relevant regional planning authorities to facilitate making appropriate decisions to combat water erosion and reclaim affected areas.